Utilization of Injectable Drugs for Communicable and Non-communicable Diseases in Primary Healthcare: A Retrospective Study in Turkey - Çolak, Selcan Tülü; Vızdıklar, Caner; Aydın, Volkan; Ayaz, Başak Dönertaş; Alkan, Ali; Akıcı, Ahmet (European Journal of Therapeutics, 2023)
Objective: Primary care, which is often the first level of contact for patients with various communicable diseases (CDs) and noncommunicable diseases (NCDs), might exhibit patterns of injectable drug utilization different from hospitals. We aimed to examine injection prescribing to adults with CD or NCD in primary care. Methods: In this retrospective study, single-diagnosis injectable drug-containing prescription data from Family Medicine Information System comprising 32 provinces of Turkey were analysed. The prescriptions were grouped by diagnosis as “CD” (n=3848) and “NCD” (n=9338). Injectable drug utilization patterns in these groups were analysed by demographics, diagnoses, and drug subgroups. Results: Out of 13186 prescriptions, 70.8% were issued for NCDs. NCD prescriptions were mostly generated for women and elderly (p<0.05 for both). About 63.3% (n=2948) of injectable drugs in CD prescriptions were antibiotics and 12.6% were analgesics. Cefazolin (15.2%) was the most commonly prescribed antibiotic for acute pharyngitis and acute sinusitis, and benzathine benzylpenicillin (12.8%) was the top-choice for acute tonsillitis and rheumatic fever. In NCD prescriptions, 34.0% (n=4214) of injectable agents were analgesics and 16.9% were muscle relaxants. The most frequently encountered drug in NCD prescriptions was thiocolchicoside (16.3%), which was the top-choice in all seven common musculoskeletal diagnoses. Conclusion: Muscle relaxants and analgesics were the most commonly prescribed injectable drugs for NCDs, musculoskeletal diseases in particular. Antibiotics were frequently encountered in CD prescriptions, mostly as broad-spectrum for lower respiratory tract infections (RTIs) and narrow-spectrum for upper RTIs. These findings may elucidate the issues to especially focus on regarding excessive use of injections.